DYNAMICS OF NEOPLASMS PREVALENCE AND INCIDENCE IN THE CHILDREN POPULATION OF UKRAINE AFTER CHERNOBYL ACCIDENT - Volosovets, O.P.; Kryvopustov, S.P.; Volosovets, A.O. (World of Medicine and Biology, 2019)
During 1994-2017, a high rate of growth in the incidence of neoplasms (+ 162.3%) and prevalence of neoplasms in children (+ 211.7%) has been observed in Ukraine. In all 9 oblasts with radioecological control areas, higher than national indicators of the incidence of children population for neoplasms and their prevalence were noted, with the exception of indicators of prevalence in children of Zhytomyr region and incidence of neoplasms in children of Volyn and Chernihiv oblasts. Over the past 23 years, the difference in the incidence of neoplasms among children from radioecological control areas and other oblasts has increased to 36.6%, and compared with the national indicator, the difference has increased by 23.5%. The mortality rate from neoplasms of children injured as a result of the Chernobyl accident has exceeded the national indicator of child mortality from malignant neoplasms, including by 2010. Then there was a reverse dynamics, and in 2016, the mortality rate from the neoplasms in children affected by the accident at the Chernobyl Nuclear Power Plant exceeded the national indicator again.